Enabling Students' Active Participation to Learn Human Digestive System with Learning Videos - Kusuma, I Gusti Ayu Agung Istri Dwi Yulianthi; Astawan, I Gede; Parmiti, Desak Putu (Universitas Pendidikan Ganesha, 2021)
Teachers' lack of use of learning media in online learning makes online learning seem monotonous so that students are not motivated to take part in learning. This study aims to produce a science learning video media prototype on the human digestive system in fifth-grade elementary school tested for validity. The development model used in this study is the ADDIE model. This study consisted of two media experts and two material experts, nine students, three individual test students, and six small group test students. The data collection method in this study was a questionnaire/questionnaire method to measure the validity of the learning video media. The data were analyzed descriptively by calculating the mean to find out the average score of the validity of the learning video media. This research resulted in a prototype of instructional video media that has been declared valid based on assessments made by design experts, materials experts, media experts, individual tests, and small group tests with an average of 3.25 < X < 4.00 with qualifications very good. Based on these results, the learning video media is declared suitable for science learning, especially on the human digestive system in fifth-grade elementary school.